PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MELALUI MODEL DISCOVERY LEARNING PADA SISWA KELAS V MATA PELAJARAN IPA - Sukmawati; Murniati; Kune, Syarifuddin (Jurnal Pendidikan dan Pembelajaran, 2023)
Education plays a pivotal role in shaping individuals capable of bringing positive change to society. Quality of learning is crucial in achieving this goal, particularly in the subject of Science (IPA), where appropriate learning approaches stimulate conceptual understanding and critical thinking skills. The Discovery Learning model has garnered attention as an interactive approach that fosters learner-centered environments. This quasi-experimental study investigates the effectiveness of Discovery Learning on critical thinking skills among fifth-grade students in IPA. Two experimental groups, one using Discovery Learning and the other conventional methods, were compared. Results indicated significant improvement in critical thinking skills among the experimental group, supported by descriptive and inferential analyses. Findings underscore the efficacy of Discovery Learning in enhancing critical-thinking abilities, paving the way for more effective educational strategies. Keywords: discovery learning; critical thinking skills.